Pregnancy, obstetrical and neonatal outcomes in women exposed to physician-related occupational hazards: a scoping review - Stephanie Smith; Moss Bruton Joe; Shannon M Ruzycki; Sarah Fletcher; Candace M Marsters; Lenka Stafl; Sarah Bugden; Rita Gustainis; Victoria Nkunu; Renee Reimer; Christine Hyde; Erica Dance (BMJ Open)
Objective Evidence is needed to guide organisational decision making about workplace accommodations for pregnant physicians. Our objective was to characterise the strengths and limitations of current research examining the association between physician-related occupational hazards with pregnancy, obstetrical and neonatal outcomes.Design Scoping review.Data sources MEDLINE/PubMed, EMBASE, CINAHL/ EBSCO, SciVerse Scopus and Web of Science/Knowledge were searched from inception to 2 April 2020. A grey literature search was performed on 5 April 2020. The references of all included articles were hand searched for additional citations.Eligibility criteria English language citations that studied employed pregnant people and any ‘physician-related occupational hazards’, meaning any relevant physical, infectious, chemical or psychological hazard, were included. Outcomes included any pregnancy, obstetrical or neonatal complication.Data extraction and synthesis Physician-related occupational hazards included physician work, healthcare work, long work hours, ‘demanding’ work, disordered sleep, night shifts and exposure to radiation, chemotherapy, anaesthetic gases or infectious disease. Data were extracted independently in duplicate and reconciled through discussion.Results Of the 316 included citations, 189 were original research studies. Most were retrospective, observational and included women in any occupation rather than healthcare workers. Methods for exposure and outcome ascertainment varied across studies and most studies had a high risk of bias in data ascertainment. Most exposures and outcomes were defined categorically and results from different studies could not be combined in a meta-analysis due to heterogeneity in how these categories were defined. Overall, some data suggested that healthcare workers may have an increased risk of miscarriage compared with other employed women. Long work hours may be associated with miscarriage and preterm birth.Conclusions There are important limitations in the current evidence examining physician-related occupational hazards and adverse pregnancy, obstetrical and neonatal outcomes. It is not clear how the medical workplace should be accommodated to improve outcomes for pregnant physicians. High-quality studies are needed and likely feasible.